EFFECT OF SOWING METHODS ON THE YIELD AND YIELD COMPONENTS OF WHEAT UNDER TWO SEED RATES AT SULAIMANI REGION - Khurshid, F. F. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
This experiment was implemented in the College of Agricultural Engineering Sciences fields in Bakrajo-Sulaymaniyah in two consecutive cropping seasons, 2017-2018 and 2018-2019. Two seeding rates were applied with three seeding methods, seed drill, conventional scattering pattern by centrifugal seeds spreader, and an un familiar pattern in the region, which is the overlapping pattern of grain spreading lines by the distributor. the coefficient of variance (% CV) for seeds had the best value in comparison to overlap spreading, which in turn was better than conventional scattering was 1.1, 8.2 and 47.2 for seed rate of 200 kg ha-1 and 1.7, 7.6, and 44.8 for seed rate of 160 kg ha-1 respectively. The seeding rate 200 kg ha-1 was significantly recorded higher averages for most of the studied traits. The sowing patterns had significantly superior to the overlapped grain spreading lines when it recorded 106.23 cm plant high, 341.47 spikes m-2, 43.1 grains spike-1, 38.7 g thousand grains weight, 3623.74 kg ha-1, 11379.03 kg ha-1 and 0.32 harvest index. The overlapped spreading mode also significantly superior to the conventional mode of prose.